Recognizing Prognostic and Predictive Biomarkers in the Treatment of Non-Small Cell Lung Cancer (NSCLC) with Immune Checkpoint Inhibitors (ICIs) - Giustini N (Dove Medical Press, 2021)
Nicholas Giustini, Lyudmila Bazhenova UCSD Moores Cancer Center, Department of Hematology and Oncology, 3855 Health Sciences Drive MC #0987, La Jolla, CA, 92093-0829, USACorrespondence: Nicholas Giustini 3855 Health Sciences Drive #0829, La Jolla, CA, 92093-0829 Email ngiustini@health.ucsd.eduAbstract: Immunotherapy plays a central role in the treatment of NSCLC and biomarkers predicting response to ICIs are valuable therapeutic tools. Programmed death-ligand 1 (PD-L1) immunohistochemistry (IHC) is integral in therapy selection as its positive predictive nature to ICIs in the metastatic setting is well documented. Tumor mutational burden (TMB) has undergone much study and, while results are somewhat mixed, there is evidence for its positive predictive value with ICI use. Additional markers such as tumor-infiltrating lymphocytes (TILs), gene expression profiling (GEP), mismatch repair (MMR) and microsatellite instability (MSI), somatic mutations, neutrophil to leukocyte ratio (NLR), smoking history, medication history, and immune-related adverse event (irAE) development can further guide clinicians.Keywords: NSCLC, immunotherapy, biomarkers